Language Situation and Language Policy in Sweden - D. S. Borodina (Научный диалог)
The results of the study of the current language situation in Sweden and the language policy, which is carried out in the country, are presented. The relevance of the research is due to the fact that similar processes of creating multilingual and multicultural communities are typical for many European countries. The study reviewed the factors that make up the prerequisites for the formation of the Swedish language policy. The novelty of the research is seen in the fact that the procedure of systematization of the factors that determine the interaction of the components of the language situation and language policy is developed. The results of the comparative analysis of the documents revealing the evolution of the language policy in Sweden are presented. Attention is paid to migration processes, which in the Swedish society give rise to the problem of cultural assimilation of migrants and the use of the Swedish language for inter-ethnic communication. The author presents the development of the reasons for the weakening of the Swedish language as a factor of national identification and strengthening the function of English as a language of internationalization. The author puts forward the position that minority languages can serve only as an ethnic attributes, not as a means of communication on a national scale. It is proved that the language policy is aimed at maintaining the main language - Swedish, linguistic assimilation of migrants and limiting the expansion of the English language.